Selenate triggers diverse oxidative responses in Astragalus species with diverse selenium tolerance and hyperaccumulation capacity - Szőllősi, Réka (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 The Authors. Published by Elsevier Masson SAS.. All rights reserved.